Preoperative transcatheter arterial embolization using a gelatin sponge for head and neck tumors. Issue 4 (4th July 2019) - Hashizume, Takuya; Shimohira, Masashi; Ohta, Kengo; Suzuki, Kazushi; Sawada, Yusuke; Nakamura, Yoshihisa; Suzuki, Motohiko; Murakami, Shingo; Shibamoto, Yuta
Abstract: Purpose: To evaluate the usefulness of preoperative transcatheter arterial embolization using a gelatin sponge for hypervascular head and neck tumors to reduce intraoperative blood loss (IBL).　　　　 Material and methods: Nineteen patients underwent preoperative transcatheter arterial embolization for hypervascular head and neck tumors using a gelatin sponge. The technical success rate, devascularization rate, IBL, and complications were evaluated. Angiography images obtained before and after preoperative embolization were compared in all patients, and the devascularization rate was assessed from the relative reduction rate of contrast agent volumes. Results: The technical success rate was 100%. The median devascularization rate was 95% (range, 75–100%). The median period between embolization and surgical resection was one day (range, 1–12 days). The median IBL was 122 ml (range, 0–3780 ml). Blood transfusions were required in three cases, and their IBL and devascularization rates were 850, 1959, and 3780 ml, and 75%, 90%, and 80%, respectively. There was a complication of cerebral embolism in one out of 19 cases (5%). Conclusions: Preoperative transcatheter arterial embolization using a gelatin sponge was feasible and may contribute to decreasing IBL.